2015
DOI: 10.3201/eid2106.140706
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response Relationship between Antimicrobial Drugs and Livestock-Associated MRSA in Pig Farming1

Abstract: Decreasing antimicrobial use can lower MRSA prevalence in pigs and subsequently in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 29 publications
1
58
0
Order By: Relevance
“…Re-introduction of the in ovo antimicrobial use was similarly associated with an increase in resistance in both cohorts. The temporal pattern of changes in resistance was consistent with a causal effect.The findings of this study are expanded with national-level data from Canada, reported by the Public Health Agency of Canada[22] and the Canadian Integrated Program for Antimicrobial Resistance Surveillance[23] (Figure A.4)Additionally, three studies addressed the human question indirectlythat is, they examined whether the introduction of antimicrobials was associated with increased resistance in animals and humans [24][25][26]. A cohort study of pigs and human farm residents, conducted in the Netherlands, found a significant dose-response relationship (across all farms) between the dose of antimicrobial and multi-antimicrobial-resistant livestock associated methicillinresistant Staphylococcus aureus (LA-MRSA): 16% increase in odds for a doubling of dose in pigs, and 1.2% increase in odds for a doubling of dose in humans [24].…”
mentioning
confidence: 92%
“…Re-introduction of the in ovo antimicrobial use was similarly associated with an increase in resistance in both cohorts. The temporal pattern of changes in resistance was consistent with a causal effect.The findings of this study are expanded with national-level data from Canada, reported by the Public Health Agency of Canada[22] and the Canadian Integrated Program for Antimicrobial Resistance Surveillance[23] (Figure A.4)Additionally, three studies addressed the human question indirectlythat is, they examined whether the introduction of antimicrobials was associated with increased resistance in animals and humans [24][25][26]. A cohort study of pigs and human farm residents, conducted in the Netherlands, found a significant dose-response relationship (across all farms) between the dose of antimicrobial and multi-antimicrobial-resistant livestock associated methicillinresistant Staphylococcus aureus (LA-MRSA): 16% increase in odds for a doubling of dose in pigs, and 1.2% increase in odds for a doubling of dose in humans [24].…”
mentioning
confidence: 92%
“…This potential for widespread transmission and the ramifications of treatment failures are significant, especially considering that nine of the fourteen classes of drugs labelled 'critically important' in public health are also used in livestock systems [5]. Antimicrobial use in the agricultural sector is projected to increase by 67% by the year Netherlands did document overlap between livestock (pigs) and people, the overlap was dependent on intensity of contact and was higher in farming communities [18]. These studies demonstrate that intervention efforts to limit AMR must be tailored to regional and local realities.…”
Section: Introductionmentioning
confidence: 99%
“…EU countries with a high antimicrobial usage (AMU) rank also high in their resistance levels [5]. Therefore, reduced and prudent antimicrobial usage in animals became of high interest in recent years, mainly due to the public health threat of antimicrobial resistance (AMR) development and possible transmission from the animal to the human population [6-9]. The first efforts in some EU countries show that a reduced usage of antimicrobials results in reduction of resistance levels as well [3, 10], which is the main focus of the international fight against antimicrobial resistance in animal production [11].…”
Section: Introductionmentioning
confidence: 99%